The effect of Fit-checking material and various subsequent cleaning methods on the wettability of the dentin surface: an in vitro study - VVSN RAJU, Jampana; Bheemalingeswar Rao , D; Suresh Sajjan, MC; Jitendra Babu, P; Ramaraju, AV; Manikyamba, YJB (International Journal of Dental Materials, 2021)
Background: GC Fit-checker is a modified polyvinyl siloxane impression material exclusively used to check the internal fit and improve the marginal fit of indirect restorations. An unpolymerized organic film is known to be leftover on the bonding surfaces after the silicone disclosing procedure. Residual silicone film being hydrophobic may alter the wettability of the cement to the tooth/metal surface, thus having a detrimental effect on the bond strength and retention of the restoration.  Aim: This study aimed to evaluate the wetting of luting liquid (GIC) to tooth dentin surface after application of Fit-checker and evaluate the efficiency of various surface treatments in removing the residual silicone film.Materials and Methods: Extracted human molars were mounted on the acrylic block, and the tooth occlusal surface was ground flat till the dentin exposure. All the specimens were assigned into five groups: Group 1: without application of Fit-checker (control group); Group 2: without any surface treatment after peeling off Fit-checker; Group 3: surface treatment with wet pumice; Group 4: 37% phosphoric acid treatment; Group 5: 10% polyacrylic acid treatment. Later, Type 1 Glass Ionomer Cement (GIC) liquid drop was placed on the dentin and photographs were made horizontally using a standardized procedure. Contact angles were measured using AUTOCAD software. Obtained values were statistically analyzed using the One-way ANOVA test and Tukey’s Post hoc test. Samples of each group were examined using the scanning electron microscope.Results: Statistically significant difference was observed among all the groups except between Group 4 and Group 2 (p > 0.05). SEM images of various groups showed a significant difference in roughness patterns.Conclusion: Surface treatment with pumice and the rotary brush was an effective method among the three in cleaning the residual silicone film.